Environmental protection against radioactive pollution - Birsen, N (Kluwer Academic, 2014)
Discusses: general estimation of the radioactive contamination of the territories and radiation hazardous objects; techniques and procedures of radioecological monitoring; and, techniques of determining radionuclide concentrations and species in the environment. This book also discusses the cross-border transport of radionuclides.